The Effect of Cu–Mo–S Coatings on Wear Resistance of Copper Friction Pair - Sergeev V. P. Viktor Petrovich; Zharkov S. Y.; Kalashnikov M. P. Mark Petrovich; Sungatulin A. R. (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen